"Medkulturni dialog" Evropske komisije kot nova verska toleranca in patent Jožefa II., imenovan "tolerančni" (1781) - Vinkler, Jonatan (Šolsko polje, 2010)
With the Patent of Toleration (1781), the absolutist Emperor Joseph II of Austria granted freedom of worship to Lutherans, Calvinists and members of the Greek Orthodox church living in the territory of the Habsburg monarchy, and later also to the Jews. This edict should be considered within the context of the Josephine reforms of the system of government, particularly in the light of the Emperor's efforts to modernise the Monarchy and make it economically competitive with other key powers on the European continent - especially France and Prussia. The Patent of Toleration thus fits in the broader context of Joseph's religious reforms which were driven by the Emperor's own political agendas. Th e resonance of these reforms should not beviewed in isolation from the interests of the state Church, which had been trying to consolidate its position in the Habsburg monarchy since the 16th century. Nor should one dismiss the role of Gallicanism, Febronianism or for that matter the signifi cance of the Enlightenment philosophical discussions on the nature of the state as an organisation and seat of authority. Within this latter purview falls also the rising infl uence of the cameralistic approach to state administration. Th e Patent of Toleration revoked the measures taken by the secular authority against non-Catholics between the end of the 16th and the fi rst decades of the 17th century. At the time these measures had been adopted to boost the political self-assertion of the Catholic Church: the Catholic Reformation movement was followed by the Counter-Reformation, which eventually led to the re-catholicisation of the lands under the Habsburg rule. Th e religious Roman-Catholic unifi cation of the larger part of the Habsburg monarchy (all the Cisleithan lands; under the Turkish occupation the Counter-Reformation measures did not reach very far into the Hungarian part of the empire) resulted in the changes in the culturalmilieus of individual crownlands and kingdoms (e.g. the Kingdom of Bohemia). Most significantly, it led to the economic weakening of the Habsburg monarchy due to religious emigration ,the result of which was a new demographic stratification of the Habsburg empire. The economic aspect of religious tolerance was also a key reason for Joseph II to issue the Patent of Toleration. And it is precisely this reason that has its contemporary echo today, as witnessed in the importance attached to the economic component behind various bureaucratically constructed European Commission projects such as "intercultural dialogue". This paper, which is based on historiographic resources and literature, includes the fi rst complete Slovene translation of the Patent of Toleration and a facsimile of its German original.
Keywords: toleranca; Tolerance; Habsburg Monarchy; Habsburška monarhija; jožefinske verske reforme; Tolerančni patent (1781); verska toleranca; etatizem; febronianizem; kameralistika